Sexual and reproductive health knowledge, attitude and behaviours of in-school adolescents in Benin City, Nigeria (African Journal of Biomedical Research, 2022)
Knowledge of sexual and reproductive health (SRH) and access to accurate information on it among adolescents remains a major challenge in Nigeria. This study assessed the SRH knowledge, attitudes and behaviours of in-school adolescents in Benin City, Nigeria. This cross-sectional study was carried out among 630 adolescents in Benin City. The respondents were selected using multi staged sampling technique. An adapted interviewer-administered questionnaire was used for data collection. Data analysis was carried out using IBM SPSS version 25.0 software. The mean age of the adolescents comprising 328 (52.1%) females and 302 (47.9%) males was 14.9 ± 1.3 years. Although 561 (89.0%) adolescents were aware of SRH, only 107 (19.1%) had good knowledge of it. Most of them 587 (93.2%) demonstrated positive attitude towards SRH. Thirty-nine (6.2%) were sexually active with 30 (76.9%) having their sexual debut before the age of 15 years, 14 (35.9%) had more than one sexual partner while only 13 (39.4%) consistently used condom during sexual intercourse. Seventeen (43.6%) had experienced vaginal/penile discharge, 6 (15.4%) had been tested for STIs, 25 (64.1%) had received treatment for STIs with home treatment 16 (64.0%) being the predominant choice. This study revealed that the overall knowledge of SRH among in-school adolescents in Benin City was poor, but most of them displayed a positive towards SRH. Although only few of the adolescents were sexually active, the prevalence of risky sexual behaviour was high among them and they also exhibit poor SRH seeking behaviour.